IMPROVING SELF-STUDY SKILLS OF HIGHER EDUCATIONAL INSTITUTIONS’ STUDENTS - Akramova, Nigora (Educational Research in Universal Sciences, 2023)
This article addresses the enhancement of self-study skills among students in higher educational institutions. It emphasizes the significance of fostering autonomy, deep understanding, and a commitment to lifelong learning. The discussion outlines strategies, institutional support, and monitoring mechanisms to facilitate the development of effective self-study habits. By promoting goal setting, time management, active learning techniques, and leveraging technology, the article offers practical insights into empowering students for independent learning.